TEENS AND THE HANG OUT LIFESTYLE: WHAT DRIVES TEENS SATISFACTION AND ATTITUDINAL LOYALTY? - Risca Fitri Ayuni (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction: Satisfying teens consumer group is critical to retain a larger market share in the future. Creating teens’ experience and value seems to be fundamental for enhancing both satisfaction and loyalty in cafes industry. Background Problem: This study examines the impact of customers’ experiences and the hedonic quality on teenagers’ satisfaction and attitudinal loyalty. Novelty: This study provides a new and comprehensive model of customer experience by adding hedonic value as a subjective experience to evaluate satisfaction and attitudinal loyalty. Research Method: Questionnaires were used to collect the data. Purposive sampling was chosen to select the respondents. Two hundred Indonesian teens participated in this study. In order to achieve the aim of this study, SPSS 23 and Partial Least Square (PLS) 3 were used. Seven out of ten hypotheses proposed in the study were supported. Findings: Three dimensions of customer experience (staff interaction, customer interaction and physical environment) have a significant effect on customers’ satisfaction, but only one dimension (physical environment) has an effect on customers’ attitudinal loyalty. An additional finding of this research is that all the hedonic quality dimensions (except hedonic emotional) have an effect on customers’ satisfaction. Lastly, customers’ satisfaction has a significant effect toward customers’ attitudinal loyalty. Conclusion: The findings suggested that a cafe’s manager or owner should pay attention to their customers’ experiences and their hedonic quality, in order to create customer satisfaction and enhance their attitudinal loyalty toward the cafe.